Mitochondrial DNA, restoring Beethovens music. (2nd January 2016) - Merheb, Maxime; Vaiedelich, Stéphane; Maniguet, Thiérry; Hänni, Catherine
Abstract: Great ancient composers have endured many obstacles and constraints which are very difficult to understand unless we perform the restoration process of ancient music. Species identification in leather used during manufacturing is the key step to start such a restoration process in order to produce a facsimile of a museum piano. Our study reveals the species identification in the leather covering the hammer head in a piano created by Erard in 1802. This is the last existing piano similar to the piano that Beethoven used with its leather preserved in its original state. The leather sample was not present in a homogeneous piece, yet combined with glue. Using a DNA extraction method that avoids PCR inhibitors; we discovered that sheep and cattle are the origin of the combination. To identify the species in the leather, we focused on the amounts of mitochondrial DNA in both leather and glue and results have led us to the conclusion that the leather used to cover the hammer head in this piano was made of cattle hide.